HISTORIA DE LA REANIMACIÓN DEL PACIENTE QUEMADO - Navarro Coto, José Francisco (2011)
Since it was proven in 1863 that fluid loss wasthe cause of death in burnt patients, a number offormulas and therapeutic options have beenestablished with the aim of improving thepatients’ survival. The Parkland ́s formula andthe use of Ringer’s lactate have been the twomethods with the best results. The use of colloidsand hypertonic solutions as well as gelatins havebeen analyzed however, there hasn’t been animprovement in the patient’s survival on thecontrary, the adverse effects have beendocumented in various revisions and clinicaltrials.